Determinants of Firm Value with Dividend Policy as The Moderating Variable - Yuliyanti, Leni; Nugraha, Nugraha; Disman, Disman; Solikin, Ikin; Mulyana, Dendi (Universitas Pendidikan Indonesia, 2024)
This research aims to investigate how profitability, capital structure, and firm size affect firm value. It also seeks to ascertain whether dividend policy can moderate the influence of profitability, capital structure, and firm size on firm value. The observational data in this study amounts to 340, obtained from 68 companies in the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. The data were sourced from the companies' financial statements published on the website https://www.idx.co.id. This study employs the Moderated Regression Analysis (MRA) model. The results indicate that profitability and capital structure have a positive but not significant impact, while firm size has a significantly negative impact on firm value. The interaction of profitability, capital structure, and firm size with dividend policy is significantly positive, meaning that dividend policy strengthens the influence of profitability, capital structure, and firm size on firm value. The implication of these findings is that dividend policy can be used as a reference in formulating company policies to enhance firm value.